ENTREPRENEURSHIP EDUCATION TO SHAPE THE CHARACTER OF VOCATIONAL STUDENTS IN FACING THE CHALLENGES OF 4.0 ERA - Misra Nofrita; Ali Idrus (Universitas Brawijaya, 2022)
Entrepreneurship education in vocational schools is vital because vocational schools have a unique and complex education system. Vocational education has the opportunity to generate students with practical abilities, knowledge, and skills for work. Such skills and knowledge are crucial to welcome the 4.0 industrial revolution era requiring human resource quality improvement. Therefore, this study reviews the importance of entrepreneurship education in vocational schools, especially in facing the challenges of the 4.0 era. We used a literature study method to analyze the related literature and discuss these issues. We conclude that entrepreneurship education is essential to shape the character of vocational students because such schools accommodate students with competencies for work. Hence, graduates are expected to create job vacancies and set up their businesses. Therefore, we need character-building to support students’ entrepreneurial spirit, and thus, it needs help from the community and the government. The community needs to trust vocational schools to produce graduates prepared for work and create job vacancies. The government also needs to trust the graduates by providing space to work well.